Facile synthesis of three-dimensional hierarchical Co3O4 peony-like microspheres and their lithium storage performance. (July 2015) - Che, Hongwei; Liu, Aifeng; Liang, Shunxing; Zhang, Xiaoliang; Mu, Jingbo; Bai, Yongmei; Hou, Junxian
Graphical abstract: The as-synthesized Co3 O4 peony-like microspheres exhibit high lithium storage capacity and good cycling performance, having a discharge capacity of 975 mA h g −1 at 100 mA g −1 after 50 cycles. Highlights: 3D hierarchical Co3 O4 peony-like microspheres have been prepared. The peony-like microspheres consist of nanosheets with a thickness of 30 nm. The Co3 O4 morphology can be controlled via adjusting the reaction parameters. The Co3 O4 peony-like microspheres reveal superior lithium storage performance. Abstract: Three-dimensional hierarchical Co3 O4 peony-like microspheres have been successfully synthesized via a facile ethylene glycol mediated solvothermal method combined with a subsequent calcination. The as-prepared peony-like microspheres are assembled by many intercrossed nanosheets with a thickness of 30 nm. The reaction conditions such as the amount of hexadecyl trimethyl ammonium bromide and sodium acetate as well as the solvothermal time are investigated to explore the effects on the morphology of the final Co3 O4 products. According to these experiment results, a possible formation mechanism of the peony-like microspheres is proposed. Furthermore, when evaluated as anode materials for lithium storage, the Co3 O4 peony-like microspheres exhibit high lithium storage capacity and good cycling performance, having a discharge capacity of 975 mA h g −1 at 100 mAg −1 after 50 cycles.